The Relationship between Exposure Tobacco Smoke in Pregnant Women with Perinatal Death in Jember Regency - Reny Ekawati; Supangat Supangat; Hairrudin Hairrudin (Journal of Agromedicine and Medical Sciences, 2019)
Perinatal death is an indicator of the success implementing a country's health services. Perinatal death rate in Indonesia in 2012 was 26/1000 live births. In 2017 there were 225 cases of infant mortality from 34,669 births in Jember Regency. Perinatal death is influenced by maternal, infant, health services and the living environment. The environmental conditions of the residence can be affected by cigarette smoke. The aim of this study was to determine the relationship of exposure tobacco smoke in pregnant women with perinatal death in Jember Regency and to find out the main source of exposure tobacco smoke in pregnant women in Jember Regency. Type of research is analytic observation with case control study design. The sampling technique is consecutive sampling. The study sample was mothers who had a dead baby in the perinatal period (perinatal death) who resided in the Jember regency on the birth of January-December 2017. The sample size was 30 for each group. Collected data was carried out by univariate analysis and bivariate analysis using the chi-square test and fisher exact test if the chi-square test requirements were not met. Results of univariate analysis in this study showed that 89.47% of the main sources of exposure tobacco smoke originated from home and 73.68% from husbands. Results of the chi-square test between exposure tobacco smoke with perinatal death p value 0.579 (p> 0.05). Confounding variables that had no significant difference between the case and control groups were parity (p = 0.116, p> 0.05), education (p = 0.083, p> 0.05), birth distance (p = 0.26, p> 0.05), and birth attendants (p = 0.492, p> 0.05). Based on the results of these studies it can be concluded that exposure tobacco smoke in pregnant women is not associated with perinatal death and the main source of exposure tobacco smoke in pregnant women comes from home and at most from husbands. Keywords: exposure tobacco smoke, pregnant women, perinatal death